Reversible intercalation of iodine monolayers between on-surface synthesised covalent polyphenylene networks and Au(111). Issue 15 (6th April 2017) - Rastgoo-Lahrood, Atena; Lischka, Matthias; Eichhorn, Johanna; Samanta, Debabrata; Schmittel, Michael; Heckl, Wolfgang M.; Lackinger, Markus
Abstract : Exposure of covalent networks on Au(111) to iodine vapour at room temperature results in mere co-adsorption, whereas elevated surface temperatures promote reversible detachment by intercalation of an iodine monolayer. Abstract : We report on post-synthetic decoupling of covalent polyphenylene networks from Au(111) by intercalation of a chemisorbed iodine monolayer. The covalent networks were synthesised by on-surface Ullmann polymerization of 1, 3-bis( p -bromophenyl)-5-( p -iodophenyl)benzene precursors on Au(111) under ultra-high vacuum conditions. The present study relates to previous work, where successful detachment was demonstrated on Ag(111) by a combination of microscopic and spectroscopic techniques. On the more reactive Ag(111) surfaces, intercalation was readily accomplished by exposing the samples to iodine vapour at room temperature. On more noble Au(111), however, STM, XPS and NEXAFS consistently indicate that the same protocol merely results in co-adsorption of iodine on uncovered surface areas, whereas the covalent networks remain adsorbed on the metal. Yet, performing the iodine exposure at elevated surface temperatures similarly results in detachment of the organic networks via intercalation of an iodine monolayer also on Au(111) as evidenced by characteristic changes in STM. In addition, owing to the high thermal stability of the covalent networks and the comparatively low iodine desorption temperature, the reversibility of the process is demonstrated: sample annealing at 400 °C results in complete desorption of the iodine monolayer, whereby the covalent networks re-adsorb directly on Au(111).